Implementation of Customer Late Payment Penalties in Murabahah Contracts in Islamic Banking Based on Fatwa DSN-MUI - Novia Prima; Ryan Bianda; Abdul Rochim (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the application of late payment penalties (ta’zir) in murabahah contracts at Bank Syariah Indonesia’s Purwakarta Branch and to assess their compliance with DSN-MUI Fatwa No. 17/DSN-MUI/IX/2000. The method used is qualitative with a case study approach through observation, interviews with relevant parties, and a review of contract documents and internal procedures. The results of the study indicate that the implementation of murabahah is conducted transparently, while late payment penalties are imposed through a verification process to distinguish between customers who are capable but intentionally delay payment and those experiencing force majeure. Penalties are calculated in accordance with the terms of the contract but are flexible, as they may be waived through specific policies for cooperative customers. The handling of late payments is conducted in stages and prioritizes consultation. Penalty funds are not recognized as bank revenue but are channeled as social funds. These findings indicate that the application of ta’zir is consistent with the provisions of the fatwa and reflects Sharia compliance oriented toward justice and the public interest.